3D PRINTING TECHNIQUE TO DOCUMENT AND PRESERVE TRADITIONAL DESIGNS OF CHANNAPATNA TOYS - Kanchana, M. Kamakshi (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Dasara Doll festival is a tradition during the Navaratri Hindu festival celebrations in South India. The festival of Navratri is celebrated in a very interesting and unique way at homes, which is commonly known as Bombe Habba or Golu or Kolu (Kannada) or Bommala Koluvu (Telugu) or Bommai Kolu (Tamil) or simply Dasara dolls. This tradition involves a toy festival that is celebrated by families across Karnataka and Andhra Pradesh, Tamil Nadu. Family toys are arranged and displayed to invited guests as part of the festival. Channapatna town close to Bangalore and Mysore is the hub of the toy making industry catering to the demand for such toys. Artisan families have been engaged in the manufacture of toys for many centuries. Designs and manufacturing techniques remained within artisan families and the knowledge transfer is through word of mouth from parents to children. Kondapalli Toys of Andhra Pradesh are made by artisans in Kondapalli which is located close to Vijayawada in Andhra Pradesh and has a similar history. The changing lifestyles in the present day have altered the way festivals are celebrated, and the patronage of such traditional crafts is on the decline. The creation of an express highway between Bangalore and Mysore has changed the road route and bypassed Channapatna town reducing the footfalls at the retail shops which sold toys for hundreds of years. Artisans are forced to explore other avenues of employment and the risk of losing the art technique is real. The portfolio of designs is dwindling, and many models are very rare and difficult to obtain from the market; they become antique collection pieces of a few individuals. Conserving the designs through CAD techniques and making prototypes using 3D printing is an effective way to preserve them. CAD documentation can be used to train a new generation of artisans or enthusiasts across the country. This will open new markets for the products and will sustain the art and design. This paper attempts to outline the technique and make a few 3D-printing prototypes with detailed drawings and present the results.